ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATERI SPLDV BERDASARKAN TAHAPAN KASTOLAN - Rohmah, Anita; Mahmudah, Wilda (Prodi Pendidikan Matematika FKIP Universitas Madura, 2024)
The purpose of this research is to find student’s errors when they solve story problems related to SPLDV material, by referring to the theory of Kastolan’s approach. This research is descriptive quantitative type. The population and sample of the study were students of class VIII MTs. Mambaul Hisan Sidayu, totaling 20 students. The data collection method involves a written test with one item of SPLDV story problems as a research tool. The results of this study showed three types of errors: conceptual errors 40% (8 students), procedural errors 70% (14 students), and technical errors 60% (12 students). So that all the errors made by students of class VIII MTs. Mambaul Hisan Sidayu as many as 34 errors with the total percentage of errors 56,7%. Analysis of the results shows that procedural errors are more common than other types of errors. Overall, lack of understanding of the meaning of the given problem is the main factor that causes students to make mistakes when solving SPLDV story problems, lack of mastery of SPLDV material, and lack of accuracy in performing calculations.